Pengaruh Kualitas Produk Dan Persepsi Harga Terhadap Keputusan Pembelian Motor Bekas (Survei Pada Konsumen PT. Adira Kota Tasikmalaya) - Yanto Herdianto; Suci Putri Lestari; Depy Muhamad Pauzy (Jurnal Publikasi Ilmu Manajemen, 2023)
This study aims to determine the effect of product quality and price perceptions on purchase decision motorcycle at PT. Adira. The method used is a case study, data obtainwed through questionnaires to the number of potential customers who are interested or not to buy a used motorcycle. Withdrawal of samples using purposive sampling technique and the method of analysis used is multiple linear regression analysis method, so the results of the regression equation are as follows: Y = 6.608 + 0.118X1 + 0.627 X2 From the research results show that product quality, price perceptions and purchasing decisions are included in the classification Very good. Simultaneously product quality and price perceptions have a significant effect on purchasing decisions for PT. Adira City of Tasikmalaya. Partially the product quality variable has a significant effect on the decision to buy a used motorbike from PT. Adira Tasikmalaya, as well as the price perception variable has a significant effect on the decision to buy a used motorbike from PT. Adira Tasikmalaya.